A Portrait of Multidimensional Poverty of Indonesian Agricultural Households - Maulini Septya; Neng Kamarni; Dodi Devianto (PT Mattawang Mediatama Solution, 2024)
The problem of poverty is not only measured by purchasing power but also by access to fulfillment of needs such as education, health, and quality of life. Poverty measured from this perspective is referred to as multidimensional poverty. This study aims to identify the multidimensional poverty conditions of households in the agricultural sector, which is the sector that contributes the highest monetary poverty rate in Indonesia. The data used is data from the National Socio-Economic Survey (SUSENAS) from 2017 to 2021. This research was conducted on 34 provinces in Indonesia. The portrait of multidimensional poverty is processed using the Alkire-Foster method using three dimensions, namely the dimensions of education, health, and quality of life. The three dimensions are measured using thirteen indicators that have been adjusted to the indicators in SDG'S 2030. The results of this study state that the deprivation of agricultural households is still high in the indicators of years of schooling, ownership of health insurance and availability of proper sanitation. The province with the highest Multidimensional Poverty Index (MPI) value is Papua, followed by four other provinces, namely, East Nusa Tenggara, Banten, West Nusa Tenggara, and West Java. In addition, this study also identifies multidimensional poverty in the agricultural sector by regional classification and gender of the household head.